Participation in Cervical Screening by Older Asian and Middle Eastern Migrants in New South Wales, Australia - Nayyereh Aminisani; Bruce K Armstrong; Karen Canfell (Tabriz University of Medical Sciences, 2012)
Background: There is little information on the detailed patterns of cervical screening uptake in older migrant women in Australia. This linkage study was performed to assess cervical screen-ing participation in older migrants.Methods: We linked year 2000-2001 records for 14,228 Middle Eastern/Asian-born women 40-64 years of age, and an age and area matched random sample of 13,939 Australian-born wom-en in the New South Wales (NSW) Admitted Patients Data Collection (APDC), which records country of birth, to screening register records. Screening behaviour after 1st July 2001 was as-sessed in women without a recorded prior cervical abnormalityResults: Compared to Australian-born women, women born in South Central Asia had a low-er screening participation rate (odds ratio for being screened at least once within a 3 year period 0.78, 95% CI 0.70-0.88). However, participation appeared relatively higher (17%-25%) in women born in the Middle East or other parts of Asia. Screening increased with increasing socioeconom-ic status (SES) in Australian-born women, but this trend was not observed in the migrant wom-en. When we broadly corrected for hysterectomy, the apparent excess of screening in women from the Middle East and other parts of Asia was substantially eliminated and in contrast, the apparent deficiency in screening in women from South Central Asia increased.Conclusions: Older women from the Middle East, and North East and South East Asian countries appeared to have similar overall screening participation to that of Australian-born women. Women from South Central Asia appeared less likely than Australian-born women to participate in cervical screening at the recommended interval.